Towards a novel fruit crop : Micropropagation and genetic transformation of the indigenous fruit tree marula, Sclerocarya birrea subsp.caffra - Mollel, Margaret Huruma Naftali (University of Limpopo ( Turfloop campus), 2005)
The marula tree (Sclerocarya birrea subsp. caffra), an indigenous, multipurpose, drought tolerant tree of Africa harbors great economic potential. Acceptance of marula-derived products internationally will directly increase the demand for marula resource. Rapid multiplication of marula trees of superior quality forms the basis of sustainable export growth. In vitro propagation and genetic improvement offer the opportunity for accelerated multiplication of selected tree material as well as to dramatically increase production, quality and efficiencies. The objectives of the study were therefore to develop a protocol for in vitro multiplication of marula and to determine the feasibility of Agrobacterium-mediated transformation of the marula tree. Nodal sections with axillary bud (s) were cultured on Murashige and Skoog (MS) medium supplemented with 4.8μM BA and 2.4μM KN and 0.1% polyvinylpyrrolidone (PVP) to obtain on average 2.5 microshoots per responding explant. The proliferated microshoots were elongated on MS medium supplemented with 1.2μM BA and 1.0μM KN. Elongated microshoots were rooted in MS medium at half salts strength supplemented with 10μM IBA and 0.3% activated charcoal (AC). On average 82% of the shoots rooted. Survival of acclimatized plantlets was 90%. RAPD analysis confirmed intraclonal genetic stability between parent plants and their clones within the limits of the technique.Nodal sections cocultivated with Agrobacterium tumefaciens for 3 days on MS multiplication medium supplemented with 100μM acetosyringone resulted on average in transient expression of 52.5% of the explants with 1.6 blue stained zones per explant. Cocultivated explants on MS selection medium containing 300mgl-1 kanamycin resulted in 1.5% chimeric putative transgenic shoots. This is the first report on the micropropagation and genetic transformation of marula, Sclerocarya birrea subsp caffra.
Thesis ( PhD. (Biotechnology )) --University of Limpopo, 2005
Keywords: Micropropagation; Genetic transformation; Indigenous fruit tree marula; Sclerocarya birrea subsp.caffra; Anacardiaceae; Fruit-Genetics.; Plant propagation-In vitro.; Food-Biotechnology.